Analytical study of the model of capsule formation of the system “Food lipids – calcium alginate” - Neklesa, Olga; Yarantseva, Yevgeniia; Pyvovarov, Yevgen; Grinchenko, Olga (Eastern-European Journal of Enterprise Technologies, 2017)
At present, a direction of the encapsulation of raw materials, different in origin, is very important in the food and pharmaceutical industries, as evidenced by numerous scientific studies into this issue the world over. The use of ionotropic polysaccharides makes it possible to provide lipid food systems with fundamentally new properties. They enable obtaining traditional oils, fats, and mixtures in the dosed form and in individual edible packaging. This promotes perception of lipid raw material as a product with fundamentally new properties that may change the structure of many technological processes. We substantiated a technique for obtaining seamless capsules with the contents of food lipids, which allowed us to determine physical parameters for the formation of a thermally-stable capsule. It was established that the formation of the resulting lipid capsule with preset organoleptic indicators is possible under conditions of individual structural design of an extrusion head for encapsulation. We derived dependences of the time of formation of the thermodynamic stable capsule “food lipids – Alg2Ca” on the magnitudes that serve as parameters of technological process – the concentration of AlgNa, calcium ions, dimensional characteristics of a capsule, mass ratios of a shell-former and the lipid contents, design features of the device that enable capsule rotation around its axis. This makes it possible to receive a stable controlled technological process. It was found that the axial rotation of a capsule in the laminar flow of accepting medium at speed which is ensured by a special design of the device, allows the formation of capsules with preset organoleptic, product, technological properties over the analytically determined time